(Bad) Random Math Proofs

Proof: 0=1

-20 = -20
16 – 36 = 25 – 45
4– 4*9 = 5– 5*9
4– 2(4)(9/2) + (9/2)2 = 5– 2(5)(9/2) + (9/2)2
(4 – 9/2)2 = (5 – 9/2)2
4 – 9/2 = 5 – 9/2
4 = 5
4 – 4 = 5 – 4
0 = 1

Proof: 1=2

x2 – x2 = x2 – x2
x(x-x) = (x+x)(x-x)
x(x-x)/(x-x) = (x+x)(x-x)/(x-x)
x = (x+x)
x = 2x
x/x = 2x/x
1=2

Proof: 1=-1

1=1
1=sqrt(1*1)
1=sqrt(-1*-1)
1=sqrt(-1)*sqrt(-1)
1=i*i
1 = -1


Read more on Mathematical Fallacy / Invalid Proof


Leave a Reply

Your email address will not be published. Required fields are marked *